Data algorithmic dependencies and their features vicissitude in relation sets - Pliuskuvienė, Birutė; Adomėnas, Petras (Lietuvos matematikos rinkinys, 2005)
This article presents introduction of the new mechanism to the relation model, particularly algorithmic dependencies showing up among attributes, which are realization of concrete applicable task structured in primary data sets. The conception of algorithmic dependencies, classification, general expressions and changes are also defined.